Emergencies in diabetes – diabetic ketoacidosis and hyperosmolar hyperglycaemic state. (February 2021) - Patel, Mayank
Abstract: Diabetic ketoacidosis (DKA) and hyperosmolar hyperglycaemic state (HHS) are life-threatening emergencies in diabetes. Prompt clinical suspicion and confirmation of these diagnoses is vitally important. Protocol-based treatment, involving intravenous fluids and electrolyte replacement in both cases, with intravenous insulin used in DKA (but not always in HHS) and close monitoring, can then be commenced to reduce associated morbidity and mortality. Every effort should be made to identify the cause, so that future preventive measures can be taken. Review by a diabetes team can ensure that diabetes treatment regimens are appropriate, educational updates are provided and patient follow-up is arranged to reduce the risk of recurrence.